A secure multicast protocol with copyright protection. - Chu, Hao-hua
We present a simple, efficient, and secure multicast protocol with copyright protection in an open and insecure network environment. There is a wide variety of multimedia applications that can benefit from using our secure multicast protocol, e.g., the commercial pay-per-view video multicast, or highly secure military intelligence video conference. Our secure multicast protocol is designed to achieve the following goals. (1) It can run in any open network environment. It does not rely on any security mechanism on intermediate network switches or routers. (2) It can be built on top of any existing multicast architecture. (3) Our key distribution protocol is both secure and robust in the presence of long delay or membership message. (4) It can support dynamic group membership, e.g., JOIN/LEAVE/EXPEL operations, in a network bandwidth efficient manner. (5) It can provide copyright protection for the information provider. (6) It can help to identify insiders in the multicast session who are leaking information to the outside world. We have implemented a prototype system which validates our secure multicast protocol and evaluated it against various performance matrices. The experimental results are very encouraging, but also show where new engineering approaches need to be deployed to conform fully to the design goals.
Keywords: Computer systems organization; Computer communication networks; Network protocols; Information systems; Information interfaces and presentation; Multimedia information systems; Computing milieux; Legal aspects of computing; Hardware/Software Protection; Copyrights; Design; Experimentation; Performance